Determination of the effective dose of dexmedetomidine to achieve loss of consciousness during anesthesia induction - Mu, Bing; Xu, Wenjie; Li, Hongyi; Suo, Zizheng; Wang, Xiaoxiao; Zheng, Yuxiang; Tian, Yi; Zhang, Bowen; Yu, Jie; Tian, Naiyuan; Lin, Nan; Zhao, Dan; et al. (Frontiers in Medicine, 2023)
Background Dexmedetomidine (DEX) is a sedative with greater preservation of cognitive function, reduced respiratory depression, and improved patient arousability. This study was designed to investigate the performance of DEX during anesthesia induction and to establish an effective DEX induction strategy, which could be valuable for multiple clinical conditions. Methods Patients undergoing abdominal surgery were involved in this dose-finding trial. Dixon's up-and-down sequential method was employed to determine the effective dose of DEX to achieve the state of “loss of consciousness”, and an effective induction strategy was established with continuous infusion of DEX and remifentanil. The effects of DEX on hemodynamics, respiratory state, EEG, and anesthetic depth were monitored and analyzed. Results Through the strategy mentioned, the depth of surgical anesthesia was successfully achieved by DEX-led anesthesia induction. The ED50 and ED95 of the initial infusion rate of DEX were 0.115 and 0.200 μg/kg/min, respectively, and the mean induction time was 18.3 min. The ED50 and ED95 of DEX to achieve the state of “loss of consciousness” were 2.899 (95% CI: 2.703–3.115) and 5.001 (95% CI: 4.544–5.700) μg/kg, respectively. The mean PSI on the loss of consciousness was 42.8 among the patients. During anesthesia induction, the hemodynamics including BP and HR were stable, and the EEG monitor showed decreased α and β powers and increased θ and δ in the frontal and pre-frontal cortices of the brain. Conclusion This study indicated that continuous infusion of combined DEX and remifentanil could be an effective strategy for anesthesia induction. The EEG during the induction was similar to the physiological sleep process.